SEARCH FOR EXCLUSIVE CHARMLESS B-MESON DECAYS WITH THE DELPHI DETECTOR AT LEP - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1995)
Charmless hadronic decays of beauty mesons have been searched for using the data collected with the DELPHI detector at the LEP collider. Several two, three and four-body decay modes have been investigated. Particle identification was used to distinguish the final states with protons, kaons and pions. Three candidate events selected in two-body decay modes are interpreted as evidence for charmless B decays. No excess has been found in higher multiplicity modes and improved upper limits for some of the branching ratios are given. © 1995.